Agitational Work for Providing Domestic Political Stability in North Caucasus Region: History, Practice, Experience - Gennady Viktorovich Marchenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with the experience of the communications work in the North Caucasus region in different periods of Russian history. Special attention is paid to the problems of propaganda effect on the locals. This research reveals the issues of information and training work and its necessity for the military officers and officers from security and law enforcement agencies in the context of realization of the state policy to ensure public safety and order in the region in the late XX - early XXI centuries.